CHAOS THEORY OF LAW: PENJELASAN ATAS KETERATURAN DAN KETIDAKTERATURAN DALAM HUKUM - . Sudjito (Mimbar Hukum, 2015)
It is of no posibilitiy to understand the complex reality of law by means of linear-mechanistic approach used to be ulitilized in rechtsdogmatiek or legal-positivism which is still dominant in the teaching of law. It needs our readiness to see the world of law not as in order but in chaos; and this is the basic reason to present the Chaos theory of law. It is hoped that this theory will enable us to explore and explain the law throroughly. Thus the law science will be the total science which does not limit itself to the positive law, the state law or the lawyer’s law. Furthermore this chaos theory is expected to give better description and comprehension of law. Order and disorder are not opposant, or white-black dichotomy, but they are interrelated, interwoven and having mutual fulfilment in a sustainably and continually change process. The Chaos theory of law, thus, constitutes a theory which is qualified to give good explanation of the complex reality of law and provide the best solution to the critical condition of law in our country.